1, 2‐Azaborine: The Boron‐Nitrogen Derivative of ortho‐Benzyne1. (11th June 2015) - Edel, Klara; Brough, Sarah A.; Lamm, Ashley N.; Liu, Shih‐Yuan; Bettinger, Holger F.
Abstract The BN analogue of ortho‐benzyne, 1, 2‐azaborine, is generated by flash vacuum pyrolysis, trapped under cryogenic conditions, and studied by direct spectroscopic techniques. The parent BN aryne spontaneously binds N2 and CO2, thus demonstrating its highly reactive nature. The interaction with N2 is photochemically reversible. The CO2 adduct of 1, 2‐azaborine is a cyclic carbamate which undergoes photocleavage, thus resulting in overall CO2 splitting.